Sejarah, Transformasi, dan Konsekuensi Game Online - Febriany, Febriany (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2022)
The development of Information and Communication Technology has made major changes in our lives. The presence of New Communication Technology has also changed the way humans communicate. Starting from using the telephone to now with the internet, social media and online games. Online games are not only used for entertainment but to interact with many people. Along with the development of technology, online games have also undergone a transformation from games played on computers to games that can also be played on smartphones.